2023
DOI: 10.1002/adma.202211438
|View full text |Cite
|
Sign up to set email alerts
|

Fluid Flow Templating of Polymeric Soft Matter with Diverse Morphologies

Abstract: It is challenging to find a conventional nanofabrication technique that can consistently produce soft polymeric matter of high surface area and nanoscale morphology in a way that is scalable, versatile, and easily tunable. Here, the capabilities of a universal method for fabricating diverse nano‐ and micro‐scale morphologies based on polymer precipitation templated by the fluid streamlines in multiphasic flow are explored. It is shown that while the procedure is operationally simple, various combinations of it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…These might explain a variable morphology with varying degrees of aggregation in the solid state in scanning electron microscopy (SEM) images (Figure S5). 53 Zetapotentials were determined to be between +29 and +56 mV for the quaternary ammonium-functionalized polymer nanoparticles (Figure 3b), with LP41 having the highest zetapotential value (56.1 ± 5.0 mV) among the materials studied here.…”
Section: Resultsmentioning
confidence: 93%
“…These might explain a variable morphology with varying degrees of aggregation in the solid state in scanning electron microscopy (SEM) images (Figure S5). 53 Zetapotentials were determined to be between +29 and +56 mV for the quaternary ammonium-functionalized polymer nanoparticles (Figure 3b), with LP41 having the highest zetapotential value (56.1 ± 5.0 mV) among the materials studied here.…”
Section: Resultsmentioning
confidence: 93%
“…Various studies have predicted 16 and measured 17 the influence of mixing on particle formation and crystallization processes. Additionally, it has been observed that flow regimes affect the shapes of particles formed in solutions, with simple-shaped particles formed under laminar flow and more complex particles under turbulent flow 18 .…”
Section: Discussionmentioning
confidence: 99%
“…Velev and Stoyanov and co-workers studied how the laminar or turbulent flow of injection of polymer solution into sheared non-solvent media results in polymer particles with shapes varied from elongated spheres to complex, large surface area structures like tubes and dendritic morphologies. [65,66] Although these structures are not envisaged for DDS, the author postulated their approach applies to many polymers, including PLA, PCL, and other common biodegradable polymers. The flow approach is scalable, and further elaboration of the method of other biodegradable polymers is envisaged for shape-controlled DDS.…”
Section: Fabrication Methods For Shape Anisotropy and Its Challengesmentioning
confidence: 99%